Potential for biological control of sclerotium foot rot of chilli by trichoderma spp. - J., Jinantana; Meon, Sariah (Universiti Putra Malaysia Press, 1998)
Air-dried preparations of Trichoderma harzianum and T. virens were evaluated for their survival and potential as biocontrol candidates against Sclerotium foot mt of chilli (Capsicum annuum, L) singly or as mixtures incorporated into organic fertilizers Amina, Avanti Green and Green Supergro as carriers. T. harzianum and T. virens incorporated singly into Amina and Avanti Green remained viable for 180 days but when incorporated into Green Supergro lost viability rapidly to zero after 30 days storage. The performance of the biocontrol candidates was also significant with Amina when tested in the artificially-inoculated soils. In the field, the incorporation of an organic carrier only improved initial establishment of the biocontrol candidates. The incidence of Sclerotium foot rot was significantly reduced with the reduction in the viable sclerotia of the pathogen and recovery of the biocontrol candidates in the chilli Thizosphere and mots was high. T. virens was a better candidate, giving 100 and 92.1 % control of Sclerotium foot rot in the artificially-inoculated and naturally - infested soils respectively.